Vanderpump Rules: A LibGuide - Rogers, Lia (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
This is a summary of a presentation delivered at FIP 2024 by Lia Rogers about a LibGuide created by Lia Rogers and Kat Lauro approaching Vanderpump Rules from an academic standpoint. We conceived the work as a LibGuide targeted towards media, communications, or English undergraduates and graduate students who are taking a popular reality television class with reality TV or Vanderpump Rules being a key text. We wanted to introduce the Vanderpump Rules as a text and engage with it with two avenues. The first, through an academic lens on reality television as a genre. The other through an understanding of how fan culture and cast engagement outside the boundaries of the episodes impacts how we consume and understand reality television. This part of our guide understands that fan engagement and voyeurism are an important aspect of consuming reality television, and this is even desired by the producers.